Changes in the texture of butternut squash following thermal treatment - B. SLASKA-GRZYWNA; A. BLICHARZ-KANIA; A. SAGAN; R. NADULSKI; Z. HANUSZ; D. ANDREJKO; M. SZMIGIELSKI (Chiriotti Editori, 2016)
Samples of butternut squash were heated in a convection steam oven at the temperature of 80°C and 100°C without any/or with addition of steam. The most significant changes of texture properties in the pulp were registered regarding its hardness and chewiness, while the alterations of its springiness and cohesiveness occurred within a smaller range. The decisive influence on changing the hardness and chewiness of butternut pulp was observed for the addition of steam, and, to a lower extent, for the time and temperature of treatment; in case of springiness the vital factor was the temperature of the process.